Casual academics: a new public management paradox. (2nd January 2017) - Ryan, Suzanne; Connell, Julia; Burgess, John
ABSTRACT: Like most management ideologies, New Public Management, is paradoxical in practice. In the case of universities, New Public Sector Management (NPM) practices have led to a core academic workforce that is tightly controlled in conjunction with a peripheral workforce of casual academics paid on hourly contracts. We examine this paradox through the experiences of academic managers responsible for casual academic employment at an Australian university. The line management of casual academics is informally delegated to subject coordinators. We conclude that the management of casual academics not only highlights the contradictions between efficiency and effectiveness in NPM practices, but, given the increased reliance on casual academics, also threatens the future of tenured academics and the 'idea of a university'.